ANALISIS PENGARUH KEMISKINAN DAN KETIMPANGAN PENDAPATAN TERHADAP PERTUMBUHAN EKONOMI INKLUSIF DI INDONESIA - Muhammad Bilal; Amsah Hendri Doni (Adisam Publisher, 2025)
The aim of this research is to measure and analyze how much influence Poverty and Income Inequality have on inclusive economic growth. This research uses a quantitative type of research using observation and literature review data collection techniques. The Classical Assumption Test uses the normality test, heteroscedasticity test, multicollinearity test and autocorrelation test. Next, use the Multiple Linear Regression Test, Determinant Coefficient Test (R^2), Hypothesis Test using the T Test (Partial) and F Test (Simultaneous). The results of data analysis carried out using EVIEWS version 13 software, the results of data analysis obtained from the t test show t count -14.16574 < t table 2.009575 with a probability value of 0.0000 which means it is smaller than 0.05 H_0 is accepted and H_1 rejected, which means that the Poverty variable (X1) partially has a significant influence on inclusive economic growth (Y). In the Income Inequality variable (X2), the calculated t value is -9.377378 with a probability value of 0.0000 which means it is smaller than 0.05, H_(0) is accepted. H_2 is not accepted which means that the Income Inequality variable (X2) partially has a significant influence. towards inclusive economic growth (Y). Judging from the f test, the calculated f value is 0.0000, which means it is smaller than 0.05. H_0 is accepted. H_1 is not accepted. This means that the variables Poverty (X1) and Income Inequality (X2) together have a significant effect on inclusive economic growth (Y). From the results, the determinant coefficient (R^2) is 0.931258. This shows that 93.1% of the Poverty and Income Inequality variables influence inclusive economic growth and 6.67% is explained by other factors.